Learning at the interstices; locating practical philosophies for understanding physical/virtual inter-spaces. Issue 5 (3rd July 2016) - Savin-Baden, M.; Falconer, L.
ABSTRACT: Virtual worlds are relatively recent developments, and so it is tempting to believe that they need to be understood through newly developed theories and philosophies. However, humans have long thought about the nature of reality and what it means to be "real." This paper examines the three persistent philosophical concepts of Metaxis, Liminality and Space that have evolved across more than 2000 years of meditation, contemplation and reflection. Our particular focus here is on the nature of the interface between the virtual and the physical: at the interstices, and how the nature of transactions and transitions across those interfaces may impact upon learning. This may, at first, appear to be an esoteric pursuit, but we ground our arguments in primary and secondary data from research studies in higher education.